Adaptive, Multisensorial, Physiological and Social: The Next Generation of Telerehabilitation Systems - Navarro, Elena; González, Pascual; López-Jaquero, Víctor; Montero, Francisco; Molina, José P.; Romero-Ayuso, Dulce (Frontiers in Neuroinformatics, 2018)
Some people require special treatments for rehabilitating physical, cognitive or even social capabilities after an accident or degenerative illness. However, the ever-increasing costs of looking after an ageing population, many of whom suffer chronic diseases, is straining the finances of healthcare systems around Europe. This situation has given rise to a great deal of attention being paid to the development of telerehabilitation systems, which have been designed to take rehabilitation beyond hospitals and care centers. In this paper, we propose which features should be addressed in the development of telerehabilitation systems, that is, they should consider adaptive, multisensorial, physiological and social aspects. For this aim, the research project Vi-SMARt is being conducted for evaluating whether and how different technologies, such as virtual reality, multi-sensorial feedback, or telemonitoring, may be exploited for the development of the next generation of telerehabilitation systems. Beyond traditional aural and visual feedback, the exploitation of haptic sense by using devices such as haptic gloves or wristbands, can provide patients with additional guidance in the rehabilitation process. For telemonitoring, Electroencephalography (EEG) devices show signs of being a promising approach, not only to monitor patients’ emotions, but also to obtain neuro-feedback useful for controlling his/her interaction with the system and thus to provide a better rehabilitation experience.